Bibliometric Analysis of Nusantara Cultural Research in Elementary Schools in Indonesia - Nisya, Khoirun; Wasino, Wasino; Arcindy, Argitha; Armaidi, Indriana Eko (Journal of Multidiscipline and Collaboration Research, 2025)
The main problem in basic education in Indonesia is the decline in understanding and appreciation of the culture of the archipelago. The tide of globalization, technological developments, and the dominance of foreign popular culture have caused local values to be increasingly marginalized, resulting in students having little knowledge of their national identity. This study aims to analyze trends in research on the culture of the archipelago in Indonesian elementary schools during the period 2020–2025, focusing on dominant themes, keyword connections, and their developmental dynamics. The analysis is expected to identify research gaps and provide recommendations for study directions relevant to culture-based education. The research method uses bibliometric analysis with the help of VOSviewer software. The data is visualized through three approaches, namely network visualization to map the connections between keywords, overlay visualization to see time trends, and density visualization to measure the intensity of research themes. The results show that the main topics include character education, cultural values, local wisdom, strengthening character, and revolution 4. The keyword “cultural” plays an important role, while “local wisdom” and “revolution 4” are increasingly dominant. This study provides a comprehensive map of the direction of research on the culture of the Indonesian archipelago and emphasizes the importance of integrating cultural values into the elementary school curriculum.